Análise dos conflitos envolvendo povos indígenas sob o prisma da visão territorial: o caso da Usina Hidrelétrica de Belo Monte - Tereza Cristina Mota dos Santos Pinto (2023)
The thesis research deals with the tension between the assumptions of Brazilian legislation and the sociocultural organization of indigenous peoples through different views of the land, based on the case of the Belo Monte Hydroelectric Power Plant. The guiding question of this work is the possibility of harmonizing the legal precepts of the Democratic State of Law and the form of political and social organization of the indigenous peoples in the scenario of construction and operation of great works and activities in the Amazon, notably the Hydroelectric Power Plant of Belo Monte, minimizing the inherent conflicts, especially those related to the land issue. The chosen methodology involved qualitative research, associated with the collection and analysis of texts, of an interdisciplinary nature, permeating areas such as Environmental and Legal Sciences, Sociology and Geography, through the study of the case in question. From there, the methodological procedures listed provided the fundamental foundation for the path from the “case to the research”, reaching the discussion about the invisibility of indigenous peoples and the disregard of minorities, to lead to land conflicts involving indigenous peoples, given their view of use and ownership, based on the chosen case study. In this way, the need for practical compatibility of different perspectives of ownership and use of land is emphasized, considering the peculiar vision within these communities, which is confused with the very essence of life and constitutes ties that direct the way of being and relating with the world.